2012
DOI: 10.1117/1.jbo.17.10.107004
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of selected species of pathogenic bacteria using near-infrared Raman spectroscopy and principal components analysis

Abstract: ABSTRACT. A method, based on Raman spectroscopy, for identification of different microorganisms involved in bacterial urinary tract infections has been proposed. Spectra were collected from different bacterial colonies (Gram-negative: Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa and Enterobacter cloacae, and Gram-positive: Staphylococcus aureus and Enterococcus spp.), grown on culture medium (agar), using a Raman spectrometer with a fiber Raman probe (830 nm). Colonies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…The detected main characteristic peaks of S. aureus were at the wavenumbers of 1006, 1158 and 1522 cm −1 , E. coli at 732, 782, 1006, 1123, 1334, 1584 and 1663, and P. aeruginosa at 750, 833, 923, 1125, 1310, 1455 and 1585 cm −1 . The detected bacteria spectra are very consistent with the spectra libraries that are shown in previous reports3334353637. In addition, Gram positive ( S. aureus ) and Gram negative ( E coli and P. aeruginosa ) bacteria discrimination are easy and rapid without requiring complex sample treatment.…”
Section: Resultssupporting
confidence: 89%
“…The detected main characteristic peaks of S. aureus were at the wavenumbers of 1006, 1158 and 1522 cm −1 , E. coli at 732, 782, 1006, 1123, 1334, 1584 and 1663, and P. aeruginosa at 750, 833, 923, 1125, 1310, 1455 and 1585 cm −1 . The detected bacteria spectra are very consistent with the spectra libraries that are shown in previous reports3334353637. In addition, Gram positive ( S. aureus ) and Gram negative ( E coli and P. aeruginosa ) bacteria discrimination are easy and rapid without requiring complex sample treatment.…”
Section: Resultssupporting
confidence: 89%
“…In Figure S3, no enhancement is found for the membrane’s Raman shift, however, the shifts at 1132, 1250, 1303, 1458, and 1578 cm −1 are enhanced in the Tip-in spectrum. These shifts are assigned to the polypeptides and the carbohydrates of the peptidoglycan layer 29–31 . The region of 1070–1650 cm −1 concludes many other Raman shifts that belong to amino acids 32 and DNA bases 33 , thus different spectrum is observed for every bacterial species.…”
Section: Resultsmentioning
confidence: 99%
“…The use of optical fibres for light delivery and collection is important as it allows interrogation of remote samples, which is highly beneficial in medical applications. Additionally, Raman spectra (or SERS spectra) have rarely been recorded in bacterial samples using fibre-optic systems [10,11] due to the reduced signal collection efficiencies and high background levels that such devices often suffer from. Here, using a fibre-optic spectrometer, we recorded Raman spectra from live E. coli and observed qualitative agreement with literature.…”
Section: Discussionmentioning
confidence: 99%
“…The use of optical fibres to deliver excitation and to collect the scattered Raman signal provides a route to minimally invasive medical use and Yang et al recently reported the detection of the bacteria Shewanella oneidensis MR-1 in aqueous solution using a fibre-optic SERS probe [10]. Additionally, de Siqueira e Oliveira et al [11] used an optical fibre based Raman probe to study multiple bacterial species that are involved in urinary tract infections (UTIs), a common type of SSI. Using this system, they were able to successfully discriminate between different pathogenic species using a diagnostic algorithm based on principal component analysis (PCA) of the acquired Raman spectra.…”
Section: Introductionmentioning
confidence: 99%